Synthesis of Several New Copoly [N – (allyl) – Substituted Imides – Methyl Acrylate] and Curing the Unsaturated Resins by Free Radical Polymerization - O.Al – Tamimi, Intisar; I, Al –Hiety, Muna; S. Omar, Lathetha (Iraqi Journal of Science, 2023)
Several new copolymer containing imides were prepared from the correspondingcopolymers containing amic acids using dehydrating agent such as acetyl chloride –tri ethyl amine mixture. The obtained yields were different ranging from 65% to80%. Readily polymerized unsaturated copolymers containing imides free radicallyusing azobisisobuty ronitrile (AIBN) as initiator to yield high molecular weightcopolymers. All the prepared resins were characterized IR. NMR. Elementalanalysis. TG and DTG Techniques.